Influence Service Quality And Price On Customer Satisfaction At Irian Supermarket Aksara - Mutriani Tafonao; Edward Alezandro; Adiwima Zebua (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2025)
This research is motivated by business competition in the retail sector in the form of minimarkets, self-service supermarkets which is increasingly tight, making business actors flock to maintain the continuity of their companies so that they remain the choice for consumers to shop, so the role of marketing is very important. The method used in this research is quantitative. The technique used in this research is probability sampling with simple random sampling of 58 respondents. The results of data processing using the SPSS 16 program in the Coefficients table for the first regression coefficient of the service quality variable show that the calculated t value is 6,695 > t table of 2.004 so that H1 is accepted and H0 is rejected. In the Model Summary table, it can be seen that the R Square value is 0.644 or 64.4%, which means that the independent variables price and service quality influence the dependent variable of consumer decision by 64.4% and the remainder is influenced by other factors not examined in this research.